Classroom Action Research (CAR) Guidance and Article Writing Techniques for Chemistry Teachers in Limapuluh Kota District High School - Alizar Ulianas (Fakultas MIPA Universitas Negeri Padang, 2019)
Classroom action research (CAR) guidance and related material and supporting PTK activities have been carried out. This activity was attended by 20 participants from high school chemistry teacher teachers in Limapuluh Kota District. This activity needs to be carried out to improve the quality of learning for teachers and find solutions to learning problems encountered in the classroom. In addition, this activity is also to help teachers fulfill the mandate of Menpan No. 84/1993 dated December 24, 1993, which was amended to become Minister of State Regulation PAN and RB no. 16 of 2009 concerning teacher functional positions and credit numbers as one of the elements of professional development in the form of research including classroom action research. This activity has been carried out by analyzing the need for guidance material by the teacher and their level of understanding of the material delivered after carrying out the activities. The results of the analysis of the need for the material of this activity were held indicated that 100% of the total participants stated that it was necessary and very necessary. While the results of the participant's understanding of the activity material were 74.29% to 93% of participants expressed understanding and were very understanding. From this analysis it can be concluded that this activity is beneficial for teachers to carry out PTK and write articles on PTK results.